Morphology of restructuring of the bone tissue of the alveolar process of the junk in the area of the lost first molar - Stupnytskyi І.-О. Р.; Rozhko М. М.; Stupnytskyi Р. М. (Actual Dentistry, 2022)
Summary. The aim of the work was to study the morphological restructuring of the alveolar process of the jaw in the area of lost teeth, as a mechanism that causes local atrophy of the bone tissue in this area. In the course of the studies, it was found that the morphological manifestations of dysfunctional atrophy in each part of the alveolar process depend on the structural features of the bone tissue and physiological conditions. It should be noted that an increase in the process of bone tissue resorption in local dysfunctional atrophy occurs against the background of unchanged appositional growth of the alveolar process.